Unique Dimerization Topology and Countercation Binding Modes in 12‐Metallacrown‐4 Compounds. Issue 32 (12th September 2022) - Salerno, Elvin V.; Foley, Collin M.; Marzaroli, Vittoria; Schneider, Bernadette L.; Sharin, Max D.; Kampf, Jeff W.; Marchiò, Luciano; Zeller, Matthias; Guillot, Régis; Mallah, Talal; Tegoni, Matteo; Pecoraro, Vincent L.; et al.
Abstract: Seven dimeric metallacrowns (MC) based on Ln[12‐MCM(III)N(shi) ‐4], where Ln III =Dy, Ho, Yb, or Y, M III =Mn or Ga, and shi 3− is salicylhydroximate, have been synthesized and characterized by single‐crystal X‐ray diffraction, and for the dysprosium‐manganese dimers, the magnetic properties have been measured. In each dimer two Ln[12‐MCM(III)N(shi) ‐4] units are linked by four bridging dicarboxylate anions (isophthalate, trimesate, dinicotinate, or 2, 2′‐dithiodibenzoate). Three different countercations (sodium, gallium(III), or pyridinium) were used to maintain charge balance of the dimer. While pyridinium does not bind to the dimer, the choice of the dicarboxylate dictates where the countercations Na + or Ga III bind. With isophthalate and trimesate, the sodium ion binds to the central MC cavity opposite of the Ln III, and with dinicotinate the sodium or gallium(III) ions bind to the pyridyl nitrogen of the dinicotinate. All three Dy2 Mn8 dimers exhibit an out‐of‐phase magnetic susceptibility signal consistent with a shallow barrier to magnetization relaxation. Abstract : The structures of seven dimeric heterometallic metallacrowns are described. Each dimer consists of two 12‐metallacrown‐4 units (ring metals Mn 3+ or Ga 3+ ) linked together by dicarboxylate anions (isophthalate, trimesate, dinicotinate, or 2, 2′‐dithiodibenzoate). Each metallacrown unit also contains one lanthanide ion bound to the central cavity. Lastly, the magnetism of the dysprosium‐manganese dimers is examined, and each display slow magnetic relaxation.